Walk this way, fly that way: Goniozus jacintae attunes flight and foraging behaviour to leafroller host instar. Issue 4 (20th February 2021) - Aspin, Emma; Keller, Michael A.; Yazdani, Maryam; Hardy, Ian C.W.
Abstract: Parasitoids exhibit distinct behaviours while foraging for their herbivorous hosts. Some are specialised with respect to the host stage they can utilise and even the age of individuals within a single stage. Observing the behavioural response of parasitoids to hosts of varying age may provide more practical understanding of potential biocontrol agents. A wind tunnel experiment was conducted to test for host‐stage dependent foraging behaviour in Goniozus jacintae Farrugia (Hymenoptera: Bethylidae), a common but understudied parasitoid of the light brown apple moth (LBAM), Epiphyas postvittana (Walker) (Lepidoptera: Tortricidae), which is a pest of grapevine, Vitis vinifera L. (Vitaceae), and other crops in Australia. Goniozus jacintae was already known to parasitise instars 3‐6 of LBAM, but most readily parasitises the later instars. Later instars are larger and have a higher rate of feeding, producing more faeces and silk deposits than earlier instars, and are likely to also produce more volatile cues that may be detected by parasitoids. We found that the timing, frequency, and duration of foraging behaviours of G. jacintae varied significantly among host instars. Flight duration was shortest when females were exposed to leaves infested by fifth instars. The profile of behaviours exhibited was different during pre‐ and post‐flight foraging, with the newly described slow walking behaviour only exhibited in close proximity to a potential host. These results contribute to the understanding of bethylid foraging, a relatively unexplored aspect of bethylid reproductive behaviour, and towards enhancing the efficacy of utilising G. jacintae in the control of leafroller pests. Abstract : In a wind tunnel experiment, we observed the foraging behaviour of the bethylid Goniozus jacintae (Hymenoptera: Bethylidae) towards four susceptible instars of the light brown apple moth, Epiphyas postvittana (Lepidoptera: Tortricidae). The frequency and duration of behaviours, flight timing, and susceptibility to attack varied significantly among host instars. These results contribute to the understanding of bethylid foraging, a relatively unexplored aspect of bethylid reproductive behaviour, and towards enhancing the efficacy of utilising G. jacintae in the control of leafroller pests.